Serial circulating tumour DNA analysis during multimodality treatment of locally advanced rectal cancer: a prospective biomarker study. Issue 4 (2nd February 2018) - Tie, Jeanne; Cohen, Joshua D; Wang, Yuxuan; Li, Lu; Christie, Michael; Simons, Koen; Elsaleh, Hany; Kosmider, Suzanne; Wong, Rachel; Yip, Desmond; Lee, Margaret; Tran, Ben; et al.
Abstract : Objective: For patients with locally advanced rectal cancer (LARC), adjuvant chemotherapy selection following surgery remains a major clinical dilemma. Here, we investigated the ability of circulating tumour DNA (ctDNA) to improve risk stratification in patients with LARC. Design: We enrolled patients with LARC (T3/T4 and/or N+) planned for neoadjuvant chemoradiotherapy. Plasma samples were collected pretreatment, postchemoradiotherapy and 4–10 weeks after surgery. Somatic mutations in individual patient's tumour were identified via massively parallel sequencing of 15 genes commonly mutated in colorectal cancer. We then designed personalised assays to quantify ctDNA in plasma samples. Patients received adjuvant therapy at clinician discretion, blinded to the ctDNA results. Results: We analysed 462 serial plasma samples from 159 patients. ctDNA was detectable in 77%, 8.3% and 12% of pretreatment, postchemoradiotherapy and postsurgery plasma samples. Significantly worse recurrence-free survival was seen if ctDNA was detectable after chemoradiotherapy (HR 6.6; P<0.001) or after surgery (HR 13.0; P<0.001). The estimated 3-year recurrence-free survival was 33% for the postoperative ctDNA-positive patients and 87% for the postoperative ctDNA-negative patients. Postoperative ctDNA detection was predictive of recurrence irrespective of adjuvant chemotherapy use (chemotherapy: HR 10.0; P<0.001; without chemotherapy: HR 22.0; P<0.001). Postoperative ctDNA status remained an independent predictor of recurrence-free survival after adjusting for known clinicopathological risk factors (HR 6.0; P<0.001). Conclusion: Postoperative ctDNA analysis stratifies patients with LARC into subsets that are either at very high or at low risk of recurrence, independent of conventional clinicopathological risk factors. ctDNA analysis could potentially be used to guide patient selection for adjuvant chemotherapy.